NATURAL PRODUCT SUBSTITUTION PATTERN AND SKELETAL RECOGNITION METHOD - Alvarenga, SAV; Rodrigues, G. D.; Gastmans, J. P.; Emerenciano, V. D. (Harwood Acad Publ Gmbh, 1995)
This work describes a methodology for identification of skeletal types of diterpenes based on data base with 1500 compounds isolated from Asteraceae. One program named BOTOCSYS was built with the codification of the compounds and their botanical sources. An example of identification of a new substance is given.
Keywords: ASTERACEAE; DITERPENES; STRUCTURAL DETERMINATION; COMPUTATION METHODS; BOTANICAL DATABASE; CHEMOSYSTEMATIC